2013
DOI: 10.12806/v12/i1/34
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Tools in the Leadership Classroom

Abstract: Social media is becoming more prevalent in the higher education classroom. As part of an ongoing study, the Department of Agricultural Leadership, Education, and Communications at Texas A&M University surveyed leadership students about their perceptions of their level of comfort and frequency of use of social media tools and the advantages and disadvantages that these students perceived when social media was used in the leadership classroom. A total of 79 students were surveyed in two upper level leadership co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…This is about 62.8% of all respondents. This observation agrees with other studies which concluded that social media could comfortably facilitate the learning process for college students, if used appropriately (Chawinga 2017;Odom et al 2013;Qureshi, Raza & Whitty 2014).…”
Section: Comfortability With the Use (Ease Of Use) Of Social Media Toolssupporting
confidence: 92%
“…This is about 62.8% of all respondents. This observation agrees with other studies which concluded that social media could comfortably facilitate the learning process for college students, if used appropriately (Chawinga 2017;Odom et al 2013;Qureshi, Raza & Whitty 2014).…”
Section: Comfortability With the Use (Ease Of Use) Of Social Media Toolssupporting
confidence: 92%
“…Their output was more meaningful because they had authentic readers. These findings concurred with [34] claim. He claimed that language students learning through new technologies can produce meaningful output.…”
Section: Enjoyable Lessons Another Main Perception Put Forth By the P...supporting
confidence: 91%
“…Furthermore, as students show a higher level of comfort using Facebook, it helps them in increasing the quality and the efficiency of communication between students and instructors [34]. Social networking services increase motivation and build confidence for students in using and learning English, help students to build and improve their vocabulary and provide a platform for teachers to prepare the lesson efficiently such as pre-writing preparation [28] [29].…”
Section: 4mentioning
confidence: 99%
“…The Personal Leadership Experiment is an example of how leadership educators can incorporate personal experimentation into their courses (see Odom et al., 2019, for a detailed overview of this assignment). This activity requires students to identify a leadership behavior or skill, develop and implement an action plan for practice of the selected behavior or skill, and then reflect on the experience.…”
Section: Transformative Pedagogies Used In Academic Courses To Foster...mentioning
confidence: 99%